Pemanfaatan Limbah Sayuran Terhadap Pertumbuhan Ikan Nila (Oreochromis niloticus) di Kelurahan Liabuku Kota Baubau - Antasalam Ajo; Ismail Failu; Abdul Hadi Bone (Program Studi Agribisnis, Fakultas Pertanian, Universitas Muhammadiyah Buton, 2023)
Waste of discarded vegetables can have a negative impact on the environment to health and efforts to use it can provide benefits such as alternative feed tilapia which in turn increases people's income. This study aims to find out the effect of vegetable waste on tilapia growth. While the usefulness of this study as an input material for tilapia farmers about alternative feed for tilapia fish cultivation is seen from the growth and increasing volume of the body. This research was conducted in July to September 2021 at Liabuku Village, Bungi Subdistrict, Baubau City. The method used is an experimental method, while the design used is a Complete Random Design (RAL) with 4 treatment levels and 3 repeats, so there are 12 experimental units. For each treatment tested tilapia fish as many as 10 tails with an average weight of 13.9 grams in each container of soil pond (waring). The treatments used are: Control (Commercial Feed), A Mustard 20% + Cabbage 70% + Kale 10%, B Mustard 50% + Cabbage 40% + Kale 10%, C Mustard 60% + Cabbage 30%+ Kale 10%. The results showed that feeding a combination of kale and bran feed had no real effect on absolute weight growth, survival rates and feed conversion. The highest absolute weight growth rate in C (Sawi is 29.55 grams). And the lowest at A is 27.47 grams. The highest survival rate on the controls (pellets) was 99% and the lowest at A at 93%. Feed conversion rate was highest at C at 10.89% and lowest at A at 15.05%.